Analisis Prosedur Pengembangan Lembar Kerja Peserta Didik Elektronik Berbasis Liverworksheet di Kelas V MI Ziyadatul Iman - Dara Julita; Nasyariah Siregar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The rapid development of technology requires education to adapt to more interactive learning innovations. One manifestation of this is the availability of various digital learning tools, including electronic learner worksheets (E-LKPD) based on Liveworksheet. However, many teachers have not optimized this interactive media, resulting in a lack of interactivity in learning. This study takes a research and development approach with the 4D development model: defining, designing, developing and disseminating. The aim is to identify the development procedure, feasibility, and practicality of electronic LKPD based on Liveworksheet. Research data were obtained through validation sheets from experts, as well as teacher and student response questionnaires in small and large group trials. The validation results showed a very high level of feasibility. Material validation reached 97%, media validation 97%, and language validation 93%, all in the “very feasible” category. Meanwhile, the level of practicality was also very satisfactory. Teacher responses reached 93.3%, indicating that they considered this media to be very practical. Similarly, students' responses; the small group trial obtained 96.3%, and the large group trial obtained 94.2%. Based on the results of the teacher and student response questionnaires, it can be concluded that the Liveworksheet-based electronic LKPD is very practical to be implemented in the learning process.